Taxation and the Sustainability of Collusion: Ad Valorem versus Specific Taxes - Helmuts Azacis; David R. Collie (Cardiff University, Cardiff Business School, 2014)
Assuming constant marginal cost, it is shown that a switch from specific to ad valorem taxation has no effect on the critical discount factor required to sustain collusion. This result is shown to hold for Cournot oligopoly as well as for Bertrand oligopoly when collusion is sustained with Nash-reversion strategies or optimal-punishment strategies. In a Cournot duopoly model with linear demand and quadratic costs, it is shown that the critical discount factor is lower with an ad valorem tax than with a specific tax. However, in contrast to Colombo and Labrecciosa (2013), it is shown that revenue is always higher with an ad valorem tax than with a specific tax.
Keywords: H21; H22; L13; L41; C72; C73; 330; Taxes; Imperfect Competition; Oligopoly; Cartel; Supergame